EMPATI SISWA MENGGUNAKAN MODEL PEMBELAJARAN IOC DAN ROLE PLAYING DENGAN MEMPERHATIKAN IQ - Amalya Oudri Windi; Edy Purnomo; Yon Rizal (JEE (Jurnal Edukasi Ekobis), 2015)
The goal of this research is to know the effectiveness of the IOC learning model and role playing to improve student empathy by looking at the intelligence quotient of eighth grade students at SMP Negeri 20 Bandarlampung years 2014/2015. Methods used in this study was a quasi-experimental. Population of this study amounted six classes, samples taken by cluster random sampling amounted two classes. The results showed: (1) theres a difference of students empathy given by IOC with a given of role playing, (2) students empathy which are given IOC is higher than students who given role playing for students who have a high level of intelligence quotient in integrated social learning, (3) students empathy which are given role playing is higher than student who given IOC for students who have a low level of intelligence quotient in integrated social learning, and (4) theres an interaction between learning model with an intelligence quotient of the empathy students.Penelitian ini bertujuan untuk mengetahui efektivitas model pembelajaran IOC dan role playing untuk meningkatkan empati siswa dengan memperhatikan intelligence quotient siswa kelas VIII SMP Negeri 20 Bandarlampung Tahun Ajaran 2014/2015. Metode penelitian ini adalah eksperimen semu. Populasi penelitian ini berjumlah 6 kelas, sampel diambil berdasarkan cluster random sampling berjumlah 2 kelas. Hasil penelitian menunjukkan: (1) ada perbedaan empati siswa yang diberikan IOC dengan siswa yang diberikan role playing, (2) empati siswa yang diberikan IOC lebih tinggi dibandingkan dengan siswa yang diberikan role playing bagi siswa yang memiliki tingkat intelligence quotient tinggi dalam pembelajaran IPS Terpadu, (3) empati siswa yang diberikan role playing lebih tinggi dibandingkan dengan siswa yang diberikan IOC bagi siswa yang memiliki tingkat intelligence quotient rendah dalam pembelajaran IPS Terpadu, dan (4) ada interaksi antara model pembelajaran dengan intelligence quotient terhadap empati siswa.Kata kunci: empati, IOC, IQ, role playing